POBREZA E CONDIÇÕES SOCIOECONÔMICAS DOS CATADORES DE CARANGUEJO DO POVOADO CARNAUBEIRAS, ARAIOSES-MA - Jean Carlos Costa Soares; Jaíra Maria Alcobaça Gomes (Revista de Políticas Públicas, 2016)
In the Lower Maranhão region Parnaíba, in the municipality of Araioses, is one of the largest communities in mangrove crab pickers of Brazil: Carnaubeiras. The town owes its importance to the large export trade crustacean to neighboring states of Piauí and Ceará as well as being situated between the major tourist routes in the country. This paper sought to understand the socioeconomic conditions of crab collectors through semi-structured interviews to understand its poverty. The results show that first, the crab collectors have low education; Second, the income of these workers do not reach the minimum wage; Third and consequently, low pay is the result of plunder by the entrepreneurs of the tourism cuisine of neighboring states; Fourth ,lack of collective organization category in coping against their exploitation; Concludes that the results obtained in this study denote the frame of poverty in the current situation of the crab hunter Carnaubeiras community.